An Integrated Platform for High-Throughput Nanoscopy - Barentine, Andrew E S; Lin, Yu; Courvan, Edward M; Kidd, Phylicia; Liu, Miao; Balduf, Leonhard; Phan, Timy; Rivera-Molina, Felix; Grace, Michael R; Marin, Zach; Lessard, Mark; Rios-Chen, Juliana; et al. (bioRxiv, 2022)
Diffraction-unlimited single-molecule switching (SMS) nanoscopy techniques like STORM /(F)PALM enable three-dimensional (3D) fluorescence imaging at 20-80 nm resolution and are invaluable to investigate sub-cellular organization. They suffer, however, from low throughput, limiting the output of a day's worth of imaging to typically a few tens of mammalian cells. Here we develop an SMS imaging platform that combines high-speed 3D single-molecule data acquisition with an automated, fully integrated, high-volume data processing pipeline. We demonstrate 2-color 3D super-resolution imaging of over 10,000 mammalian cell nuclei in about 26 hours, connecting the traditionally low-throughput super-resolution community to the world of omics approaches. Competing Interest Statement ificant financial interest in Bruker Corp. and Hamamatsu Photonics Footnotes * Added new biological application of method.